The Illusion of Papuan Independence through Benny Wenda’s Transnational Advocacy Network Strategy during the #FreeWestPapua Campaign in 2020 - Eunike Meliani Wahyuningtyas (Journal Research of Social Science, Economics, and Management, 2024)
This research reveals critically rather than using images of modern development and progress on Indigenous Papuans (OAP) who are often demanded to engage in social change by ignoring one's identity. The accumulation of OAP disillusionment that began in the history of the Act of Free Choice continued with the neglect of cultural rights as a reflection of the collective dignity that is still running. This triggered some OAP segments who called themselves independent Papuan groups to choose to garner international support in efforts to secede principles. As done by Benny Wenda as OAP through international forums to encourage the fulfillment of political rights caused by the closed access to the Papuan people's movement in fighting for the issue of Free Papua. He described the resistance of Papuan identity to expand the target domain of its supporter audience. Sporadically through the use of international civil society networks, the authors highlight the advocacy strategies undertaken Transnational Advocacy Network (TAN) through the #PapuanLivesMatter campaign that raised the existence of Benny Wenda in representing Free Papua in the midst of fragmentation that occurred. So the research questions in this study are: What is Benny Wenda's strategy in representing an independent Papua in the midst of fragmentation of separatist groups in Papua? The method for accessing the variables in the theory will be traced based on historical methods that are explained qualitatively.